2017
DOI: 10.1177/1477153517721728
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the effects of correlated colour temperature and gender on cognitive task performance

Abstract: Higher correlated colour temperature ambient lighting, which contains more blue light, has been reported to improve performance on a variety of cognitive tasks. The current investigation compared performance of adults on what/where task switching, go/no-go, and mental rotation tasks when the experimental room was lit by 3500 K standard florescent and 5000 K LED lighting. Results showed that, under higher correlated colour temperature illumination, females (but not males) decreased reaction time by approximatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 26 publications
1
18
1
Order By: Relevance
“…Contrary to our hypothesis, we found no differences between participants in each lighting condition on sustained attention. This contrasts previous findings with adults demonstrating positive impacts of higher CCT light on go/no-go task performance [ 14 , 44 ]. Accuracy on the task was high, with participants averaging approximately 80% correct on no-go trials, and both the control and experimental groups showed only minor improvement in accuracy from the baseline to test assessments, suggesting participants were performing near ceiling level.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Contrary to our hypothesis, we found no differences between participants in each lighting condition on sustained attention. This contrasts previous findings with adults demonstrating positive impacts of higher CCT light on go/no-go task performance [ 14 , 44 ]. Accuracy on the task was high, with participants averaging approximately 80% correct on no-go trials, and both the control and experimental groups showed only minor improvement in accuracy from the baseline to test assessments, suggesting participants were performing near ceiling level.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, the main effect of Phase for reaction time on switch trials suggests that children in the experimental group gained significantly greater accuracy on switch trials than participants in the control group without sacrificing speed, consistent with results from previous work measuring the relationship between young children’s speed and accuracy on measures of executive function [ 47 ]. These results extend previous findings with adult participants that exposure to higher CCT light improves performance on a task switching task [ 13 , 14 ]. Results are discussed in the context of the relationship between the built environment and development, as well as emerging trends in technology.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…28 Our alertness during the day and ability to sleep at night are affected by the amount of circadian stimulus that each individual receives during the day. 27 According to Hartstein et al, 29 people improve their ability to maintain attention and transition between tasks (more positively so for females) when exposed to a higher CCT. Even though we may experience an increased alertness at higher CCT, the cooler light at more than 5000 K is often rated less positively.…”
Section: Glare and Eyestrainmentioning
confidence: 99%